The Susceptibility of Retinal Ganglion Cells to Glutamatergic Excitotoxicity Is Type-Specific - Christensen, Ian; Lu, Bo; Yang, Ning; Huang, Kevin; Wang, Ping; Tian, Ning (Frontiers in Neuroscience, 2019)
Retinal ganglion cells (RGCs) are the only output neurons that conduct visual signals from the eyes to the brain. RGC degeneration occurs in many retinal diseases leading to blindness and increasing evidence suggests that RGCs are susceptible to various injuries in a type-specific manner. Glutamate excitotoxicity is the pathological process by which neurons are damaged and killed by excessive stimulation of glutamate receptors and it plays a central role in the death of neurons in many CNS and retinal diseases. The purpose of this study is to characterize the susceptibility of genetically identified RGC types to the excitotoxicity induced by N-methyl-D-aspartate (NMDA). We show that the susceptibility of different types of RGCs to NMDA excitotoxicity varies significantly, in which the αRGCs are the most resistant type of RGCs to NMDA excitotoxicity while the J-RGCs are the most sensitive cells to NMDA excitotoxicity. These results strongly suggest that the differences in the genetic background of RGC types might provide valuable insights for understanding the selective susceptibility of RGCs to pathological insults and the development of a strategy to protect RGCs from death in disease conditions. In addition, our results show that RGCs lose dendrites before death and the sequence of the morphological and molecular events during RGC death suggests that the initial insult of NMDA excitotoxicity might set off a cascade of events independent of the primary insults. However, the kinetics of dendritic retraction in RGCs does not directly correlate to the susceptibility of type-specific RGC death.